PENGARUH PENDIDIKAN KESEHATAN TERHADAP TINGKAT PENGETAHUAN KELUARGA TENTANG PERTOLONGAN PERTAMA PADA PENDERITA HIPERTENSI STAGE 1 - Sya'id, Achmad; Darotin, Rida; Cahyono, Hendra Dwi; Budiman, M.Elyas Arif (NHM PRESS, 2023)
Family knowledge about first aid for stage 1 hypertension is still relatively low so it is necessary to increase family knowledge by means of health education about first aid for stage 1 hypertension. Patients with Stage 1 Hypertension. Methods: quasi-experimental method with a pre-test and post-test non-equivalent control group approach using a questionnaire measuring instrument with purposive sampling technique. The number of samples taken was 36 families with stage hypertension. Results: The results obtained that after being given health education about first aid hypertension stage 1, family knowledge became good. Analysis: the results obtained by the majority after being given health education, family knowledge became good. A total of 32 respondents (89%) have good knowledge, 4 respondents (11%) have sufficient knowledge and no respondents have poor knowledge. By using the Paired Sample t-test it shows a significant number between the pretest and posttest values with a significance value (2 failed) p = 0.000 < 0.005 so that H0 is rejected and Ha is accepted. Discussion: Health education has a very important role in determining human quality, with human health education gaining knowledge and information. The higher a person's level of knowledge, the higher the quality of his life..